Export markets: substitutes, complements, or independent?. Issue 3 (6th February 2021) - Aranguren, Mari Jose; De Lucio, Juan; Mínguez, Raúl; Minondo, Asier; Requena, Francisco
ABSTRACT: Using a large sample of export transactions in Spain over the period 2010–2017, we explore whether firms treat export markets as substitutes, complements, or independent. We find that an exogenous change in revenue in a firm's top export destination does not change its revenue in other destinations. A firm does not have either a larger probability to increase the number of export destinations when it experiences an exogenous drop in revenue in its top export destination. These results suggest that a shock in firms' top export market does not affect their decisions in other export markets.